The measurement of human motion: A comparison of commercially available systems - Richards, J. G. (Fifth International Symposium on the 3-D Analysis of Human Movement, 1998)
Vergleich folgender Systeme für die Analyse der menschlichen Bewegung: Ariel, CODA, Motion Analysis, Optotrak, Peak Motus, Qualisys, Skill 6D Research und Vicon 370.